The influence of corporate financial events on selected JSE-listed companies - S. J. Ferreira; S. Mohlamme; Gary Van Vuuren; Zandri Dickason Koekemoer (Cogent Economics & Finance, 2019)
In South Africa, corporate finance events receive extensive coverage in the media. However, there are only a few studies examining the behaviour of share prices in response to such events. Using the event study methodology commonly used in corporate finance research, the reaction of a sample of large- and small-cap stocks to selected corporate finance events (such as dividend and earnings announcements, stock splits and accounting policy changes) was analysed. Results show that there is a rapid stock price adjustment immediately post-announcement, but the time taken varies depending on the nature of the event and company size. This may have profound implications on discretionary portfolio management: fund managers should find it beneficial from a diversification standpoint. Exiting from heavy concentrations in large-cap stocks and diversifying into smaller cap stocks could offer the stability of portfolio returns against adverse events like Steinhoff's accounting fraud.
Keywords: G3; G14; 330; G3aG14; total/free-float; market capitalisation; corporate finance events; semi-strong EMH; size anomaly